ABOUT THE DURATION AND ANXIETY OF THE HUMAN EXISTENCE - Кравченко, П. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The peculiarities of S. Kierkegaard’s understanding of the human essence are considered in the article. It is shown that from birth to death a human being is forming his/her own “Self” that is accompanied by fear and anxiety.